Peran Anggota Keluarga Lain dalam Komunikasi Keluarga antara Anak Perempuan dengan Single Father - Puspitasari, Annisaa Aprilia; Pratiwi, Meisyi Naishilla Defti; Permatasari, Yulia Putri Kartika (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to find out the communication patterns formed in family communication between daughters and single fathers with the help of other family members' roles in it. This study uses a narrative study approach with a constructivist paradigm to explore individual experiences and the meanings they build in their communication interactions. The informant in this study is a daughter who no longer has a mother because she died and lives at home with other family members. The results of the study indicate that the communication pattern between daughters and single fathers in this study is protective, where the communication pattern is oriented towards high conformity and low conversation. One of these is the discovery of a communication barrier, where daughters feel unable to freely open up to single fathers without a communication bridge such as other family members in the communication between them so that daughters feel less heard because fathers choose to maintain good relationships so that future conflicts can be avoided. This study also emphasizes the importance of additional supporting data in narrative studies, such as follow-up interviews, to provide a more comprehensive picture of the dynamics of communication in families between daughters and single fathers with the help of other family members' roles. By understanding the factors that influence the formation of this communication pattern, this study is expected to contribute to the development of better communication strategies in families with single parent conditions, especially single fathers, and provide insight for practitioners and researchers in the field of family communication. This study also provides practical significance for intervention efforts and social support for families facing similar challenges.